Odpowiedź :
Odpowiedź:
a.
x = 5t - 1
x + 1 = 5t
t = (x+1)/5
b.
3t = 5a
a = (3t)/5
c.
7w = 3x - 1
7w + 1 = 3x
x = (7w + 1)/3
d.
v/2 = 5t
v = 5t * 2
v = 10t
e.
2 + 5s = p
5s = p - 2
s = (p - 2)/5
f.
3a(x+e)=s
x + e = s/3a
e = s/3a - x
g.
sp = e - p + 3w
sp + p - 3w = e
h.
12s+4p=12
12s = 12 - 4p
s = (12 - 4p)/12
s = 1 - 1/3p
i.
(o+p)/w = r
o + p = rw
w = (o+p)/r
j.
(x-w)/t = q
x - w = qt
x = qt +w
k.
Cif = om
f = om/ci
l.
Rad = ur
a = ur/Rd
Odpowiedź:
a.
X=5t-1 , t
5t = x + 1 /:5
t = 1/5(x + 1)
b.
3t = 5a , a /:5
a = 3/5t
c.
7w = 3x - 1 , x
3x = 7w + 1 /:3
x = 1/3(7w + 1)
d.
v/2 = 5t , v /*2
v = 5 * 2t = 10t
v/2 = 5t t = ? /:5
t = v/10
e)
2 + 5s = p , s
5s = p - 2 /:5
s = 1/5(p - 2)
f.
3a(x + e) = s , e /:3a
x + e = s/(3a)
e = s/(3a) - x
g.
Sp = e - p + 3w , e
e = Sp + p - 3w
h.
12s + 4p = 12 ,s
12s = 12 - 4p /:12
s = 1 - 1/3p
i.
(o+p)/w = r ,w
wr = o + p /:r
w = (o + p)/r
j.
(x-w)/ t = q , x /*t
x - w = qt
x = qt + w
k.
Cif=om, f /:Ci
f = om/Ci
l.
Rad = ur , a /:Rd
a = ur/Rd
Szczegółowe wyjaśnienie:
Szczegółowe wyjaśnienie:
Szczegółowe wyjaśnienie: